Fading Ricardian Equivalence in Ageing Japan - Saito, Ikuo (IMF Working Papers; Working Paper ;, 2016)
Japan seems to be turning less Ricardian, a trend set to continue. First, the discount wedge seems to have risen, suggesting that consumers have become more myopic. Second, some evidence points to the possibility that an increasing number of households are liquidity constrained. If these developments continue, the impact of fiscal policy on the economy will gradually rise. While this will facilitate using fiscal policy to manage the economic cycle, it also calls for starting fiscal consolidation soon and in a gradual and steady manner, given the unsustainable public debt and the likely increasing challenges in funding the government's rising debt domestically.